2009
DOI: 10.1371/journal.pone.0006621
|View full text |Cite
|
Sign up to set email alerts
|

The Diagnostic and Prognostic Accuracy of Five Markers of Serious Bacterial Infection in Malawian Children with Signs of Severe Infection

Abstract: BackgroundEarly recognition and prompt and appropriate antibiotic treatment can significantly reduce mortality from serious bacterial infections (SBI). The aim of this study was to evaluate the utility of five markers of infection: C-reactive protein (CRP), procalcitonin (PCT), soluble triggering receptor expressed on myeloid cells-1 (sTREM-1), CD163 and high mobility group box-1 (HMGB1), as markers of SBI in severely ill Malawian children.Methodology and Principal FindingsChildren presenting with a signs of m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

10
50
2
4

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(66 citation statements)
references
References 27 publications
10
50
2
4
Order By: Relevance
“…However, our results contradicted the results of the studies which were done by Patenaude et al, [19] 1995 (86%) and Bharti B et al, [20] in 2008 (83.1%). The sensitivity of the C-reactive protein, which was observed in our study was 90.9%, which matched with those of the studies which were done by Heiskanen-Kosma T et al, [21] in 2000 (94.3%), by Requejo HI et al, [22] in 2003 (98%) and by Enitan D and Carrol et al, [23] in 2009 (97.2%). Our results differed from those of the studies which were done by Massimiliano Don et al, [24] in 2009 (74%) and Virkki R et al, [25] in 2002 (73.5%).…”
Section: Discussionsupporting
confidence: 92%
“…However, our results contradicted the results of the studies which were done by Patenaude et al, [19] 1995 (86%) and Bharti B et al, [20] in 2008 (83.1%). The sensitivity of the C-reactive protein, which was observed in our study was 90.9%, which matched with those of the studies which were done by Heiskanen-Kosma T et al, [21] in 2000 (94.3%), by Requejo HI et al, [22] in 2003 (98%) and by Enitan D and Carrol et al, [23] in 2009 (97.2%). Our results differed from those of the studies which were done by Massimiliano Don et al, [24] in 2009 (74%) and Virkki R et al, [25] in 2002 (73.5%).…”
Section: Discussionsupporting
confidence: 92%
“…As in previous study [1,4], serum procalcitonin level was markedly elevated in the patients with meningitis caused by hematogenous spread of bacteria. Of these patients, the patients with sequelae or complication especially had high serum procalcitonin level, indicating that it is a useful marker for the prediction of severity and prognosis.…”
supporting
confidence: 77%
“…Procalcitonin is a useful marker not only in the diagnosis of severe bacterial infection such as sepsis and bacterial meningitis but also in the prediction of the prognosis of these diseases [1]. On the other hand, serum procalcitonin level is hard to be elevated in focal infection [2,3].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Higher levels of HMGB-1 have been shown patients with fatal outcome (36,38), as well as in patients with infection as compared to healthy controls (38,40). Other studies, however, have shown no statistically significant difference in serum levels of HMGB-1 between infected and the non-infected patients (40,41), using the same commercial kit utilized in this study. In the absence of general consensus in the literature, the role of HMGB-1 remains debatable, as this molecule parallels other severity markers and may not provide further specific information regarding outcome (5).…”
Section: Discussionmentioning
confidence: 51%